Metal, Swords, and Birds. A Myth Spanning Time, Place, and Cultures - Kucypera, Paweł (Institute of Archaeology and Ethnology of Polish Academy of Sciences, 2017)
During the late 1950s, a discovery of precipitates interpreted as nitrides in the structure of Iron Age iron objects led to the forming of a hypothesis, in which deliberate nitriding of iron in the distant past was implied. The allegedly purposeful introduction of nitrogen to form compounds with iron was linked to the Þiðriks saga. There, in a fragment devoted to the making of the sword Mimming, Velent the smith feeds domestic fowl with filings from a ground down blade, which he later picks up from the birds’ droppings and reforges into a new weapon of superior quality and performance. Bafflingly, this seemingly unbelievable story appears in faraway lands, in different time periods. The paper presents the context and circumstances of the occurrence of this myth and provides a technological commentary.
il. ; 29 cm
Keywords: azotowanie żelaza; miecze; Wieland; żelaza epoka; średniowiecze